The Q hypothesis unveiled: theological, sociological, and hermeneutical issues behind the sayings source - Tiwald, Markus (Beiträge zur Wissenschaft vom Alten und Neuen Testament, 2020)
The essays collected in this volume are the proceedings of an international conference on the Sayings Source Q held in Essen, Germany in August 2019. The scholars contributing to this volume generally support the Q hypothesis. Nevertheless, they want to submit their own conceptions to scrutiny. Especially the question as to whether Q scholars are driven by unscholarly projections or prejudices was the subject of debate. Sometimes also exegetes follow trends and fashion. Therefore, the central topic of this volume is a critical self-reflection on the hermeneutical options (and perhaps also biases) in Q Research.